The Examining of Transformational and Transactional Leadership on Banking Employee Performance at North Sulawesi Province, Indonesia - Yance Tawas (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2019)
Transformational and transactional leadership style is an activity that influences people to working together in order to achieve the organization goals. Leadership can occur anywhere, provided that someone shows his ability to influence the behavior of others towards achieving a certain goal. Transformational leadership as a leader who has the power to influence subordinates in certain ways. The intent of transformational and transactional leadership is to encourage employee performance in the Banking business in North Sulawesi, Indonesia. The object of the study was Bank BRI, BNI and SulutGo, which have branches throughout the North Sulawesi region. The number of respondents was 205 employees. The collected data were then analysed by using a variant-based structural equation model or Partially Least Square (PLS-SEM). The data analysis results provide empirical evidence that a transformational leadership style, particularly in the individual consideration and individual inspirational dimensions, positively impacts employee performance. However, other dimensions, namely, intellectual stimulation and inspirational motivation, do not significantly encourage activities related to performance. Moreover, transactional leadership on the contingent reward dimension does not significantly impact knowledge sharing, in other word only transformational leadership individual consideration and individual inspiration were positively significant effect on encourage banking business industry employee performance at North Sulawesi, Indonesia. Keywords: employee performance, transformational leadership, banking company,